Deposition and Characterization of Luminescent Eu(tta)3phen‐Doped Parylene‐Based Thin‐Film Materials. Issue 9 (3rd May 2013) - Maggioni, Gianluigi; Campagnaro, Antonio; Tonezzer, Michele; Carturan, Sara; Quaranta, Alberto
Abstract Herein, novel host–guest films produced by coarse vacuum cosublimation of the parylene C dimer and Eu(tta)3phen are prepared and studied. Eu(tta)3phen sublimation at different temperatures allows films with different concentrations of the Eu complex to be obtained. The films are characterized by Rutherford backscattering spectrometry (RBS), FTIR spectroscopy, X‐ray diffraction (XRD), atomic force microscopy (AFM), and UV/Vis absorption and emission spectroscopy. RBS, FTIR, and XRD reveal the incorporation of Eu(tta)3phen into the parylene matrix. AFM evidences the very flat film surface, which is particularly advantageous for optical applications. UV/Vis absorption and emission analyses confirm that the optical properties of Eu(tta)3phen are preserved in the deposited films. Fluorescence measurements evidence the occurrence of an energy‐transfer process between parylene and Eu(tta)3phen, and this results in an increase in the light emitted by the Eu complex that is as much as five times higher than that emitted by Eu(tta)3phen alone.